Penggunaan Media Booklet Ibu Hamil dalam Upaya Pencegahan Anemia pada Ibu Hamil Korban Tsunami - Indah Trianingsih; Marlina Marlina (Politeknik Kesehatan Tanjung Karang, 2020)
Anemia has a high contribution to mortality in Indonesia with a percentage of 50-70%. The research objective was to determine the benefits of booklet media to prevent anemia in pregnant women victims of the tsunami in the South Lampung area which occurred in December 2018. The research design was pre-experimental with one group pre-test and post-test research designs. The population of this study was pregnant women who were in the South Lampung area which was affected by the December 2018 tsunami. The number of samples was the total population taken randomly. Quantitative data analysis using frequency distribution, independent T-test. Based on the results of the Wilcoxon Matched Pairs statistical test, the effectiveness of the pregnant women booklet on HB levels, the value of α=0,000 was obtained, so that α<0,05. The results of this statistical test prove that the booklet of pregnant women is effective on the HB level of pregnant women. Likewise, in the booklet effectiveness test of pregnant women on maternal knowledge, the value of α=0,000 was obtained so that α<0,05. Thus it can be concluded that there is the effectiveness of pregnant women booklets in efforts to prevent anemia in pregnant women victims of the tsunami in the South Lampung area in 2019.